OPTIMASI DESAIN KOMPONEN LENTUR GELAGAR PERSEGI BAJA - Mutiara, Tria Octa; Putrianti, Pratika Riris; Setiawan, Agustinus Agus (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2022)
The traffic congestion in Indonesia’s big city needs effective infrastructure developments within limited areas. The purpose of this study is to determine an optimum dimension of steel box girder to carry the load on every span length and yield strength of girder based on SNI 1725-2016 and SNI 1729-2015. This study is using the Microsoft Excel program and limited only the compact section of flange and web section. The analysis result shows that higher yield strength the more in weight saving. Within the weight section of the yield strength, 690 MPa has 30% in saving weight compared to 250 MPa. Than the optimal web thickness for the yield strength of 250 MPa is 15 mm and for the yield strength of 690 MPa is 13 mm. The optimum ratio for depth of the web to span length is 1/60 L.